Hsp70: A Multifunctional Chaperone in Maintaining Proteostasis and Its Implications in Human Disease - Manish Kumar Singh; Sunhee Han; Songhyun Ju; Jyotsna S. Ranbhise; Joohun Ha; Seung Geun Yeo; Sung Soo Kim; Insug Kang (Cells)
Hsp70, a 70 kDa molecular chaperone, plays a crucial role in maintaining protein homeostasis. It interacts with the DnaJ family of co-chaperones to modulate the functions of client proteins involved in various cellular processes, including transmembrane transport, extracellular vesicle trafficking, complex formation, and proteasomal degradation. Its presence in multiple cellular organelles enables it to mediate stress responses, apoptosis, and inflammation, highlighting its significance in disease progression. Initially recognized for its essential roles in protein folding, disaggregation, and degradation, later studies have demonstrated its involvement in several human diseases. Notably, Hsp70 is upregulated in multiple cancers, where it promotes tumor proliferation and serves as a tumor immunogen. Additionally, epichaperome networks stabilize protein–protein interactions in large and long-lived assemblies, contributing to both cancer progression and neurodegeneration. However, extracellular Hsp70 (eHsp70) in the tumor microenvironment can activate immune cells, such as natural killer (NK) cells, suggesting its potential in immunotherapeutic interventions, including CAR T-cell therapy. Given its multifaceted roles in cellular physiology and pathology, Hsp70 holds immense potential as both a biomarker and a therapeutic target across multiple human diseases. This review highlights the structural and functional importance of Hsp70, explores its role in disease pathogenesis, and discusses its potential in diagnostic and therapeutic applications.